Effect of Integrated Yoga on Emotional Stability and Performance of Employees: An Action Research Study - Chokkalingam,; Kumari, Sony; Akhilesh, K. B.; Nagendra, H. R. (Prabandhan: Indian Journal of Management, 2015)
Development of the performance of employees is an important concern for employees, employers, and the society at large. In this study, an important personality trait, that is, emotional stability, its importance in the performance of an employee, and the impact of the practice of Integrated Yoga on emotional stability and performance of an employee were studied; 51 employees were given Integrated Yoga intervention and another 51 employees, who comprised of the control group, were not given any intervention for 4 months. Using the Big Five Personality Questionnaire, data about emotional stability was collected from the yoga intervention group and control group before the study, in the middle of the study, and at the end of the study. The data was analyzed using SPSS, and a significant increase (p - value <0.001) in emotional stability among the subjects in the yoga intervention group was found (it was not found in the control group). So, it is concluded that the practice of Integrated Yoga improves the emotional stability, and thus the performance of the employees.